1996
DOI: 10.1021/bi9523365
|View full text |Cite
|
Sign up to set email alerts
|

Mg Coordination by Amino Acid Side Chains Is Not Required for Assembly and Function of the Special Pair in Bacterial Photosynthetic Reaction Centers

Abstract: A conserved histidine serves as the axial ligand to the Mg of bacteriochlorophylls in the photosynthetic reaction center (RC) and many other photosynthetic systems. The histidine axial ligands to each and both bacteriochlorophylls of the special-pair primary electron donor of the Rhodobacter sphaeroides RC have been replaced with glycine to create a cavity. In each case, RCs assemble and a normal special-pair comprised of Mg-containing bacteriochlorophylls is formed, as judged by many different spectroscopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 55 publications
4
72
1
Order By: Relevance
“…This is in contrast with the bacterial reaction centers where the homologous glycine replacements are practically indistinguishable from wild type (39). The largest redox effects at D1-His198 are associated with His replacement by Glu and Ser.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is in contrast with the bacterial reaction centers where the homologous glycine replacements are practically indistinguishable from wild type (39). The largest redox effects at D1-His198 are associated with His replacement by Glu and Ser.…”
Section: Discussionmentioning
confidence: 71%
“…sphaeroides reaction centers is still the preferred binding motif over the replacement of the Bchlorophyll with Bpheophytin. Goldsmith et al (39) and Schulz et al (38) have shown that replacement of the coordinating His with Gly still results in Bchlorophyll binding but with water as the likely ligand. The same is likely true of the B-His656Gly mutation of PSI (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The L168HG mutant was prepared as described previously (28). The L173HL mutant was engineered with a poly(histidine) tag at the N-terminal end of the M subunit; this poly(histidine) tag has been shown to have no effect on the properties of the RC but greatly facilitates RC isolation (29).…”
Section: Methodsmentioning
confidence: 99%
“…Ligand replacement studies on other enzymes, for example, carbonic anhydrase (26), heme-containing proteins (27)(28)(29)(30), and the bacterial reaction center (31), suggest a biochemical method by which the proton acceptor of tyrosine D can be identified. In the above investigations, a histidine residue was replaced with glycine or alanine by site-directed mutagenesis.…”
mentioning
confidence: 99%